PENCATATAN PERKAWINAN DALAM KITAB FIKIH DAN UNDANG UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN (PERSPEKTIF MAQA - Sehabudin, Sehabudin (UIN Sunan Kalijaga Yogyakarta, 2014)
In order to regulating marriage practices under the hand (Sirri) inIndonesia, the government requires the marriage of two terms: first,materil conditions, namely the conditions that are attached to each ruleof marriage, whether arranged in fiqh or set forth in the statutory.Second, the administrative conditions, namely the conditions relatingto the registration of marriage. Registration of marriage was arrangedin article 2 paragraph (2) of Indonesian Marriage Law No. 1/1974,while the registration procedures of marriage was arranged in GovernmentRegulation No. 9/1975. Regulation of registration of marriage has causedcontroversy among legal experts in Indonesia. This controversy causedby the interpretation of article 2 paragraph (1) and (2) of IndonesianMarriage Law, on the other hand, due to different interpretations of theconcept walimah and Surat al-Baqarah (2): 282. Based on the analysisof Maqasid ash-Shari’ah, registration of marriage that written in thebook of fiqh implicitly, while the UUP written explicitly, is very suitablefor the purpose of Islamic Shari’ah, because it can preserve and protectreligion, life, intellect, lineage and property before the law. Thus, thebenefit of the household (family harmony and eternal) can be achieved.